Phytoremediation Of Fish Farm Wastewater Incorporating Physical Treatment - Rajantrakumar, Navin Kumar (Universiti Sains Malaysia, 2018)
Phytoremediation has the potential for treatment and reuse of wastewater in intensive aquaculture systems. This technique serves the purpose of reducing the pollution caused by fish farming which will preserve the surface and ground water quality. In this study, the performance of phytoremediation incorporated with physical treatment by Spirodela Polyrhiza macrophytes on fish farm wastewater is investigated. The objectives of the study are to evaluate the performance of physical treatment incorporated with phytoremediation. The nutrient uptake by S.polyrhiza from the fish farm wastewater and water quality after phytoremediation was monitored. The wastewater phytoremediation by S. polyrhiza was conducted in small-scale constructed wetlands for 14 days. The results showed that filter Fendi with pore size 20 µm out-performed Sterlitech (3.0 µm) and Sartorius (0.2 µm) in terms of filtrate rate (L/m2) and costing based on the quantity required of 2 L for this experiment. Fendi showed the highest filtrate rate of 25000 L/m2 and the lowest cost for filtering 2 L of wastewater with RM 37.40. For nutrients uptake, filtered was more successful compared to control as it resulted in a lower final value at the end of day 14. The final nitrate, phosphate and ammonia level were 9.4 mg/l, 0.27 mg/l and 1.4 mg/l respectively. All three nutrient level were able to meet the standard A (applicable to discharge into any inland waters within catchment area which is the most stringent limit), discharge limit for enclosed water body. As for water quality, filtered was able to meet the Standard A for COD level and total suspended solids discharge limit achieving final value of 109 mg/l and 20 mg/l. The pH level day 14 of 7.45 was in the range of Standard A and as for turbidity it decreased from 110 NTU to 25 NTU in 14 days which was below the class IIA (water supply II) which passes for conventional treatment to produce clean drinking water. S. polyrhiza showed biomass increment for both filtered and control. This study indicates that phytoremediation incorporated with physical treatment shows a greater potential in the treating fish farm wastewater.